Domestic Regulation and Service Trade Liberalization - Mattoo, Aaditya; Sauve, Pierre (Washington, DC: World Bank, 2013)
International barriers to services trade are deeply intertwined with national regulatory, investment, and immigration policies. Accordingly, the liberalization of trade in services is considerably more complex that the liberalization of trade in goods. Sector-specific issues abound. This book sheds much light on the challenges facing the trading community in this area, through essays from a distinguished group of authors. Services liberalization has been, and will continue to be the engine of trade liberalization, if that outcome is to occur at all. The book provides one of the best guides to services trade, and all its technicalities, ups and downs, and the future of the world trade order.